An In-Depth Analysis of Covid-19 Medications and Vaccination with A Focus on Side Effects - Jishnu Banerjee; Rajdeep Ghosh; Ananya Paul; Soumyajit Banik; Sumit Halder; Joy Sarkar (Medsci Publications, 2023)
Background: A pandemic threat to public health has been posed by the SARS-CoV-2 outbreak. To deal with the severe situation caused by this outbreak, medications were used, but we weren't thinking about the potential negative effects. This review sought to evaluate the efficacy and safety of various medications in COVID-19 patients, as well as the present state of medications and their adverse effects. Methods: Several literature and databases were searched and analysed properly from 2020 to 2022 to find the relevant databases on the usage of proper medications. Results: During COVID-19, many antivirals, antibiotics, and conventional drug therapy were in high demand. Many antivirals, including Remdesivir and Ritonavir, were tried, but they had a number of adverse effects, including hypokalaemia, headaches, and nausea. Another issue with the use of drugs in this pandemic is antibiotic resistance. Since vaccines are relatively new, adverse symptoms like fever, discomfort, chills, tiredness, nausea/vomiting, headache, and insomnia have so far been reported. Conclusion: This analysis outlines a progressive change in the medical community, where simple treatment procedures have shown to be more successful than those using many drugs, producing better patient results. This indicates a shift in medical practice toward more simplified and effective modes of care.